Dance Performance as a Means of Self-Actualization of Learner in the Tradisional Dance Training Process at the Kembang Sore Dance Studio - Aufa, Salina Athaya Salsabila; Ishaq, M; Choiro, Umu Da'watul (Proceedings Series of Educational Studies, 2024)
In this research, it can be seen that: the dance performance at the Kembang Sore Dance Studio, Kediri Branch, is a place for self-actualization for residents to learn. The training process and stage performances give rise to the need for self-actualization. The aim of this research is to describe the traditional dance arts training process at the Kembang Sore Dance Studio Kediri Branch as a means of self-actualization, as well as the dance performance at the Kembang Sore Dance Studio Kediri Branch as a means of self-actualization. This research uses a qualitative research method with a case study approach. Data was collected through interviews, observation and document study. Documents were analyzed using domain analysts and processed using the Miles Huberman model. The dance performance at the Kembang Sore Dance Studio, Kediri Branch, is part of the learning process and supports students learning to express and actualize themselves in traditional dance arts.